Toward the synthesis of spirastrellolide a: construction of a tetracyclic C26-C40 subunit containing the DEF-bis-spiroacetal. - Paterson, I; Anderson, E; Dalby, S; Loiseleur, O (2005)
[reaction: see text] A stereo-controlled synthesis of the fully elaborated C26-C40 tricyclic [5,6,6]-bis-spiroacetal of spirastrellolide A containing the C28 chlorine substituent is reported, exploiting asymmetric Sharpless dihydroxylation and boron-mediated allylation methodology.